The Multitasking Fasciola gigantica Cathepsin B Interferes With Various Functions of Goat Peripheral Blood Mononuclear Cells in vitro - Chen, Dan; Tian, Ai-Ling; Hou, Jun-Ling; Li, Jie-Xi; Tian, XiaoWei; Yuan, Xiao-Dan; Li, Xiangrui; Elsheikha, Hany M.; Zhu, Xing-Quan (Frontiers in Immunology, 2019)
Cathepsin B, a lysosomal cysteine protease, is thought to be involved the pathogenesis of Fasciola gigantica infection, but its exact role remains unclear. In the present study, a recombinant F. gigantica cathepsin B (rFgCatB) protein was expressed in the methylotrophic yeast Pichia pastoris. Western blot analysis confirmed the reactivity of the purified rFgCatB protein to serum from F. gigantica-infected goats. The effects of serial concentrations (10, 20, 40, 80, and 160 μg/ml) of rFgCatB on various functions of goat peripheral blood mononuclear cells (PBMCs) were examined. We demonstrated that rFgCatB protein can specifically bind to the surface of PBMCs. In addition, rFgCatB increased the expression of cytokines (IL-2, IL-4, IL-10, IL-17, TGF-β and IFN-γ), and increased nitric oxide production and cell apoptosis, but reduced cell viability. These data show that rFgCatB can influence cellular and immunological functions of goat PBMCs. Further characterization of the posttranslational modification and assessment of rFgCatB in immunogenicity studies is warranted.